Analysis of Public Opinion on Social Media X and YouTube on the Results of the 2024 Presidential Election - Himawan Indrajat; Tabah Maryanah; Hertanto; Andri Marta (Jurnal Terekam Jejak, 2025)
This study analyzes the sentiment of social media users, especially Twitter and YouTube, on the results of the 2024 presidential election won by the Prabowo-Gibran pair. The goal is to identify the dominance of sentiment, whether positive, negative, or neutral. The research method uses a literature approach with content analysis on user responses. The data obtained showed the dominance of negative sentiment, especially criticism related to election integrity, human rights issues, and candidate feasibility. These results reflect significant public dissatisfaction with the political process, highlighting the role of social media as a reflection of public opinion. These findings provide insight for the government in understanding public perception and the importance of transparent communication to strengthen public trust in democracy.